Computational analysis of the immunogenicity and sequence diversity of Mycobacterium tuberculosis PPE_MPTR proteins - Colic, Antoinette (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.